2018
DOI: 10.1016/j.clay.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism responsible for intercalation of dimethyl sulfoxide in kaolinite: Molecular dynamics simulations

Abstract: Intercalation is the promising strategy to expand the interlayer region of kaolinite for their further applications. Herein, the adaptive biasing force (ABF) accelerated molecular dynamics simulations were performed to calculate the free energies involved in the kaolinite intercalation by dimethyl sulfoxide (DMSO). Additionally, the classical all atom molecular dynamics simulations were carried out to calculate the interfacial interactions between kaolinite interlayer surfaces and DMSO with the aim at explorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Intercalation is a promising strategy to expand the interlayer distance of clay minerals for their further exfoliation or other applications . Usually, polar molecules are intercalated into the layers in a liquid environment, swelling the layered structure and weakening the interlayer attraction.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…Intercalation is a promising strategy to expand the interlayer distance of clay minerals for their further exfoliation or other applications . Usually, polar molecules are intercalated into the layers in a liquid environment, swelling the layered structure and weakening the interlayer attraction.…”
Section: Design and Fabricationmentioning
confidence: 99%
“…The species of guest molecules that enter between the layers of kaolinite are determined by the hydrogen bonds between the octahedral and tetrahedral layers of kaolinite, therefore, a limited number of polar molecules are used to locate kaolinite clay layers in the literature. One of these molecules is DMSO, which is a polar compound [22]. For this reason, modification and intercalation processes were carried out on DMSO-spaced kaolinite.…”
Section: Characterization Of Intercalated Nanoclaysmentioning
confidence: 99%
“…The molecular mechanism of DMSO intercalation has been recently revisited using molecular dynamics simulation. The modeling confirmed that intercalation involves the hydroxyl groups of the octahedral vacancies functioning as H-donors towards the S=O group of DMSO, whereas the hydrophobic Si=O groups of the ditrigonal cavities of the tetrahedral surface attract the methyl groups of DMSO [23,24].…”
Section: Introductionmentioning
confidence: 72%